Analisis Dampak Strategi Pengembangan Sumber Daya Manusia terhadap Peningkatan Kinerja UMKM di Kabupaten Boyolali - Siti Musarofah; Kurniawan Arief Ichsanuddin; Muhammad Abiyyu Al Hammam (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the regional economy, including in Boyolali Regency. However, this contribution has not been fully matched by adequate human resources (HR). The main problem in this study is the still low capacity of MSMEs' human resources, particularly in aspects of managerial skills, digital literacy, and adaptability to changes in the business environment, which impact business performance. This study aims to analyze human resource development strategies implemented in the MSME context and examine the impact of these strategies on improving MSME performance in Boyolali Regency. The research method used is a Systematic Literature Review (SLR) with a content analysis approach to relevant scientific literature from the past five years. The research process includes determining inclusion and exclusion criteria, searching for literature sources, thematic coding, and synthesizing research findings. The results show that effective HR development strategies can be grouped into three main aspects: skills training, marketing digitalization, and cross-sector collaboration. These three strategies have been proven to contribute positively to improving MSME competency, operational efficiency, market expansion, and business competitiveness. Thus, human resource development is a key factor in driving sustainable improvement in MSME performance, particularly in facing the challenges of digital transformation and increasingly complex economic competition.